HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN KECENDERUNGAN GAYA HIDUP BRAND MINDED PADA REMAJA DI DESA PINELENG SATU - Christy Kandou; Deetje J. Kandou; Stevi B. Sengkey (PSIKOPEDIA, 2022)
This study aims to examine the relationship between parents' socioeconomic status (education, employment, income, expenses, property ownership) and the brand minded lifestyle of adolescents in Pineleng Satu Village. This research uses quantitative methods. The population is 210, the research subjects are 131 youth aged 18-22 years in Pineleng Satu Village based on the sampling technique using the Isaac and Michael formula with the sampling technique using purposive sampling. The research instrument for the scale of socio-economic status of parents by Soekanto (2010) with 23 items with valid items is 19 items and the brand minded lifestyle scale uses the brand minded lifestyle scale AIO Engel, Blackwell & Miniard (1995) With 24 items with items valid as many as 21 items. Hypothesis testing using the Spearman's Rho correlation results showed that there was a relationship between parents' socioeconomic status and brand minded lifestyle. The results of the correlation coefficient test show that there is a relationship between parents' socioeconomic status (Variable X) in detail, namely: Parents' education, occupation, income, expenses and property ownership with brand minded lifestyle (Variable Y). This shows that the H1 hypothesis is accepted which reads "There is a relationship between the socio-economic status of parents and the tendency for a brand-minded lifestyle in adolescents in Pineleng Satu Village."